PENERAPAN MODEL PEMBELAJARAN GENERATIF DENGAN SETTING KELAS KOOPERATIF STAD (STUDENT TEAM ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN PEMAHAMAN KONSEP KIMIA DAN KINERJA ILMIAH SISWA KELAS X MIPA 7 SMA NEGERI 5 DENPASAR TAHUN PELAJARAN 2016/2017 - Miyati, A.A. Rai (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2019)
This classroom action research aims to: 1) improve understanding of chemical concepts, and 2) improve scientific performance of students in chemistry learning on the subject of non electrolyte electrolyte solutions and reduction oxidation reactions. This study involved 36 students of class X MIPA 7 Denpasar Senior High School 5. The object of this research are: 1) understanding of students 'chemical concepts, 2) and students' scientific performance. Data on understanding students' chemical concepts is collected from concept understanding tests, then analyzed. The research is successful if the average conceptual understanding of students is greater or equal to 75, DSS S 75% and KK KK 85%. Data on students' scientific performance aspects are collected with a scientific performance assessment rubric. Data were analyzed using ideal mean criteria. The research is successful if qualitatively the scientific performance of students is high. The results of the analysis show: (1) The application of the generative learning model with the STAD cooperative class settings can improve the understanding of the chemical concepts of class X MIPA 7 Denpasar Senior High School 5 Academic Year 2016/2017. This can be seen from the average value of students' concept understanding of 76.30 and classical completeness of 72.22%. Student absorption is 76.30% with a standard deviation of 7.88 increasing in the second cycle of 84.07 with classical completeness reaching 94.44%. The absorption of students in the second cycle was 84.07% with a standard deviation of 5.58; (2) The application of the generative learning model with the STAD cooperative class setting can improve the scientific performance of class X MIPA 7 Denpasar Senior High School 5 Academic Year 2016/2017. This can be seen from the average value of scientific performance of students in the first cycle of 52.56 with a standard deviation of 14.76 which is in the low category increased in the second cycle to 71.36 with a standard deviation of 10.89 which is in the high category. Scientific performance of students has increased from cycle I to cycle II by 35.77%.